Perancangan Sistem Informasi Rekonsiliasi Transaksi (Bank Xyz) - Arin, Ikrar Adinata; Sihombing, J. Rolles Herwin (Bina Nusantara University, 2014)
Banking world wants to help companies accelerate transaction receipts and disbursements, of the money they save in the bank. Bank account is a means to save money and transact safely and practically. If there is a large payment to the supplier, the company does not need to carry a lot of cash to the suppliers place, simply by giving a check to the supplier, and vice versa. E-Reconciliation is a service from XYZ Bank in the form of a delivery payment transaction data to the customer server periodically. Data delivery, safe and secure, to customers is an important factor in the process of reconciliation, one safe and secure way is to send the reconciliation report via encrypted email facility. With the delivery of the payment transaction data, customers can automatically reconcile the data. E-Reconciliation including new services in banking and is expected to add value to XYZ Bank among other competitors. In addition, it is expected to be many dealers and sub-dealer/reseller of customers who are interested in using E-Reconciliation services, so as to improve the balance of CASA.